Ultrasound Promoted Fabrication of CuO‐Graphene Oxide Nanocomposite for Facile Synthesis of Fluorescent Coumarin Based 1, 4‐disubsituted 1, 2, 3‐triazoles in Aqueous Media. Issue 23 (19th June 2019) - Jain, Yachana; Kumari, Mitlesh; Laddha, Harshita; Gupta, Ragini
Abstract: Herein, we report a highly efficient sonochemical synthesis of CuO‐graphene oxide nanocomposite and its application as a recyclable catalyst for copper catalyzed azide‐alkyne cycloaddition (CuAAC) reaction of 3‐azidocoumarin derivatives and various terminal alkynes for the robust synthesis of regioselective fluorescent 1, 4‐disubsituted triazoles (3 a‐o) . This protocol includes water as a clean medium, effectively low copper loading, operational simplicity, good to excellent yield (up to 97%) in lesser time (60 min) and diverse substrate scope. Easy catalyst separation from reaction media and its recycling up to nine consecutive cycles without appreciable loss in the product yield are other noteworthy features of this protocol. The optimized reaction conditions were then explored successfully to get 90% yield at gram scale level. Abstract : Sonochemical synthesis of CuO‐graphene oxide nanocomposite and its application as a recyclable catalyst for copper catalyzed azide‐alkyne cycloaddition (CuAAC) reaction of 3‐azidocoumarin derivatives and various terminal alkynes for the robust synthesis of regioselective fluorescent 1, 4‐disubsituted triazoles (3 a‐o). This protocol includes water as a clean medium, effectively low copper loading, operational simplicity, good to excellent yield (up to 97%) in lesser time (60 min) and diverse substrate scope.